(untitled) (Nexo Revista Científica, 2022)
Improving the efficiency of technological tillage methods is primarily associated with developing existing tools and creating new types of working tools for tillage machines. Tillage efficiency improvement depends on the correct choice of the most energy-efficient working tools belonging to the same class of the technological process. This research aims to develop scientific baselines for choosing energy-efficient working tools of different structural designs based on the criteria of power consumption and quality of shallow tillage. The object of this research includes working tools for shallow and deep tillage. The research subject is the changes in the criteria chosen to evaluate the working tools’ efficiency. We involved mathematical modeling based on laws of science observed during tillage, carried out experiments and analyses, and summarised the experimental findings. The scientific novelty of this research justifies the criteria for evaluating the efficiency and quality of working tools used for shallow and deep tillage. The research relies on graphical and empirical dependencies describing the trends in efficiency evaluation criteria for tillage working tools with various operation speed modes. We discovered that to evaluate the efficiency and choose the most energy-efficient tillage working tool, one should use a system of criteria: specific tractive resistance of the active frontal area, terra-dynamic resistance coefficient, and the primary tillage quality parameters. The probability of compliance of the mean values of calculated and experimental findings (0.51–0.87) confirms the adequacy of proposed mathematical models describing changes in specific tractive resistance per unit of active frontal area and terra-dynamic resistance coefficient of tillage working tools. According to the research, when a more energy-efficient tillage working tool is chosen, the working tools under comparison belong to the same class of working tools based on the technological process principle and functioning conditions. Discovered trends in the changes in the efficiency evaluation criteria and the choice of energy-efficient tillage working tools for shallow and deep tillage are represented by empirical dependencies applicable in specific ranges of motion speed under certain functioning conditions. Consequently, we emphasized that further studies should justify the upper and the lower borders of the tillage working tools and terra-dynamic resistance coefficient in accordance with the agrotechnical quality indicators of tillage.